2021
DOI: 10.3348/kjr.2020.0592
|View full text |Cite
|
Sign up to set email alerts
|

Volume and Mass Doubling Time of Lung Adenocarcinoma according to WHO Histologic Classification

Abstract: Objective This study aimed to evaluate the tumor doubling time of invasive lung adenocarcinoma according to the International Association of the Study for Lung Cancer (IASLC)/American Thoracic Society (ATS)/European Respiratory Society (ERS) histologic classification. Materials and Methods Among the 2905 patients with surgically resected lung adenocarcinoma, we retrospectively included 172 patients (mean age, 65.6 ± 9.0 years) who had paired thin-section non-contrast ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 37 publications
2
16
0
Order By: Relevance
“…Previous studies have reported that the size of GGNs is a critical risk factor for potential invasiveness (3)(4)(5)21). Lee et al found that the optimal cutoff size for preinvasive lesions was less than 10 mm (sensitivity, 53.33%; specificity, 100%) in a pure GGN cohort; this could be used as a selection criterion to identify patients suitable for sublobar resection (25).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have reported that the size of GGNs is a critical risk factor for potential invasiveness (3)(4)(5)21). Lee et al found that the optimal cutoff size for preinvasive lesions was less than 10 mm (sensitivity, 53.33%; specificity, 100%) in a pure GGN cohort; this could be used as a selection criterion to identify patients suitable for sublobar resection (25).…”
Section: Discussionmentioning
confidence: 99%
“…We combined baseline and 3-month follow-up continuous CT scan images to obtain the original features and changed features that maximized the risk of tumor invasion. Recently, numerous studies and guidelines have advocated that early follow-up of patients with GGN should replace unnecessary surgical resection (3,5,19). However, subtle changes between the short-term follow-up images and the baseline CT images are often invisible to mostly radiologists, hence the need to evaluate invasiveness using DL algorithms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within thoracic oncology, computed tomographic (CT) quantification of volume-doubling time (VDT) has been used as a means to measure the presumed exponential nature of lung cancer growth grossly, in order to better understand time to progression 13 , 14 . VDT varies by methodology and histologic type but a recent study by Hong et al places the VDT of squamous cell carcinoma at 149 days (∼21 weeks) and adenocarcinoma ranging by subtype from 232 days or ∼33 weeks (solid/micropapillary) to 1140 days or ∼ 163 weeks (lepidic) 15 . While 21 weeks is likely much longer than any experienced delay during the lockdown, it certainly puts context to the minimum of 11 weeks delay that many New Yorkers may have experienced.…”
Section: Discussionmentioning
confidence: 99%
“…The patients with the following characteristics (Fig. 1) will be selected in this study, including (1) GGN was identi ed by a pathology, (2) pulmonary nodules were regarded as pure GGOs or part-solid GGOs based on the chest CT examination with slice thickness less than 1.25 mm, (3) the GGN was at least twice determined by chest CT scanning with an interval of over 30 days [20] , and (4) either the density, volume, or mass of GGN, estimated by the CT embedded software, was increasing, i.e., the GNN was growing. Only the largest size of GGN was recorded if multiple GNNs were detected from a patiented, these patients also included.…”
Section: Patientsmentioning
confidence: 99%